Does Sourgrass leaf anatomy influence glyphosate resistance? - Barroso, Arthur Arrobas Martins; Galeano, Esteban; Albrecht, Alfredo Junior Paiola; dos Reis, Fabrícia Cristina; Victoria Filho, Ricardo (Comunicata Scientiae, 2015)
Sourgrass(Digitaria insularis, L. Mez ex Ekman)is a weed that requires high rates of glyphosate ((N-[phosphonomethyl]-glycine) forcontrol, verylittle of the herbicide applied isabsorbed by theleaves. Morphological and histological differences in leaves of glyphosate-resistant and glyphosate-susceptible plantsshould explain the contrast of variance between herbicide susceptibility. Leaves of different growth andphenological stages were collected and submitted to histological andelectron microscopy scanning analysis. Those plants were also submitted to a glyphosate dose-response curve analysis. The results suggest thatbiotypes exhibits differences infoliar structures that can influence the uptake and translocation of glyphosate. A thinparenchyma, lesser distance amongvascular bundles, and higher phloem sizewere found in resistant biotypes (differences close to 10%). Minor stomata number and higher epicuticular waxy deposition in stomata and leaf surface were found in resistant plants when leaves came from regrowth, leading to a possiblelesser herbicide absorption. Resistant plants showed absence of trichomes in late stages of development (64% less trichomes than susceptible plants). The higher concentration of trichomes in susceptible plants can be an absorption pathfor glyphosate getthrough the cuticle.